2022
DOI: 10.1115/1.4055900
|View full text |Cite
|
Sign up to set email alerts
|

Selecting and Optimizing Origami Flasher Pattern Configurations for Finite-Thickness Deployable Space Arrays

Abstract: Design parameters of the origami flasher pattern can be modified to meet a variety of design objectives for deployable array applications. The focus of this paper is to improve understanding of design parameters, objectives, and trade offs of origami flasher pattern configurations. Emphasis is placed on finite-thickness flasher models that would enable engineering applications. The methods presented aim to provide clarity on the effects of tuning flasher parameters based on existing synthesis tools. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Within a high transition temperature environment, the design requires appropriate coupling mechanisms to minimize failures. Coupling mechanisms attribute to 10% of overall failures and thus optimization must be undertaken to maximize the durability and minimize the failure rate [21].…”
Section: General Design Objectives Of Cubesatmentioning
confidence: 99%
“…Within a high transition temperature environment, the design requires appropriate coupling mechanisms to minimize failures. Coupling mechanisms attribute to 10% of overall failures and thus optimization must be undertaken to maximize the durability and minimize the failure rate [21].…”
Section: General Design Objectives Of Cubesatmentioning
confidence: 99%
“…The thickness of the material, for example, often causes issues (ex. wrinkling, local buckling) during the coiling process [14,17,19,20], while alternate wrapping methods have been suggested that accommodate thickness [21][22][23]; these methods do not include a sealed inner volume and thus are not suitable for pneumatic actuator use.…”
Section: Party Horns and Coiled Inflatable Boomsmentioning
confidence: 99%
“…Thick plate origami is currently the mainstream research direction, which is fabricated * Author to whom any correspondence should be addressed. by assembling thin sheets made from either paper, plastic, or metal into 3D origami structure [9][10][11][12]. However, it often requires tedious assembly processes and additional binders or connection device (shaft hinge).…”
Section: Introductionmentioning
confidence: 99%